Use of complementary therapies among breast cancer patients in Hospital Universiti Sains Malaysia (HUSM) - Khair, Siti Arsih Mohamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2012)
Even though there were some researchers done the studies regarding the use of Complementary Therapies among breast cancer patients, but there were still less official data in local context. There were only a few studies done regarding this topics in Malaysian. The aim of this study was to determine the current usage of the complementary therapies used in local context and how those selected socio-demographic data were associated with the perceptions towards Complementary Therapies used among breast cancer patients. Samples were taken by purposive sampling among breast cancer patients in Hospital Universiti Sains Malaysia (HUSM) either patients that were admitted to the wards or patients who came for follow up in the outpatient clinic in HUSM (n=70). Self-administered questionnaire was used to collect the data. Data was analyzed by using the Statistical Package Social Science (SPSS) software version 18.0. Majority of the samples in this study was came from the middle age group ranged from 31 to 40 years old. There were high in percentage of respondent who's already married (64.3%) compare to another marital status. The samples also majority (62.9%) came from the average level of educational level which was completed secondary school. CTs practitioner most commonly visited by the respondents was dietician or nutritionist (98.57%), and then followed by herbalist (40.0%). Overall, 100% of the respondents reported as CTs users, most frequently used was vitamins/minerals (92.8%), and then followed by herbal remedies (82.8%). Chi-square test was used to identify the association between selected socio-demographic data and the perceptions towards CTs used. For the age, the p value was 0.004 (p<0.05), which showed that there were a significant association between age and perceptions. For the marital status, p value was 0.019 (p<0.05) which also showed that there were a significant association between marital status and perceptions. But, for the educational level, p value was not significant which p=0.473 (p>0.05), that means there were no significant association between educational level and perceptions. In conclusion, not all selected socio-demographic data had significant association with the perceptions towards CTs used.